Ingestion exposure and committed health risk of natural radioactivity and toxic metals in local rice sold in Enugu urban markets - Ugbede, Fredrick Oghenebrorie; Akpolile, Anita Franklin; Oladele, Blessing Bosede; Agbajor, Godwin Kparobo; Popoola, Felix Adegoke (Taylor & Francis, 2024)
Abstract Rice (Oryza sativa) is an important source of human internal exposure to radionuclides and heavy metals because, worldwide, a large fraction of the population consume rice as their daily basic diet. In this study, the levels and correlation of natural radioactivity (232Th, 226Ra and 40K) and heavy metals (Pb, Ni and Cd) in local rice sold in Enugu urban markets, a southeastern part of Nigeria, were examined. Possible health implications were also evaluated. The mean activity concentrations were estimated to be 235.81 ± 12.93, 54.29 ± 8.08 and 63.70 ± 3.93 Bqkg−1 for 40K, 226Ra and 232Th respectively. Obtained values were higher than values reported in the literature for rice in other locations. The estimated committed effective doses for 226Ra and 232Th exceeded the global ingestion dose average of 0.12 mSvy,–1 whereas that of 40K is below the 0.17 global average. The average concentrations of the metals were estimated to be 0.41, 3.70, and 0.02 mgkg–1 for Pb, Cd and Ni, respectively, with only Ni having an average concentration below the threshold food safety limit of FOA/WHO. Only the concentrations of Cd were of significant levels with their health risk indices exceeding the tolerable reference levels for both children and adult. Only the pairs, 232Th-Ni and Pd-Cd, correlated significantly (p < 0.05) which implies common sources. Multivariate principal component analysis indicated common natural sources for 226Ra, 232Th and Ni in local rice, possibly of lithogenic and paedogenic in nature. It is believed that the results of this study will be valuable to the radiological and toxicological food safety and policy framework of WHO/FAO in Nigeria and the rest of the world. Aquatic Science & Fisheries Abstracts (ASFA) Professional
Keywords: Natural radionuclides; heavy metals; local rice samples; correlation; ingestion; Enugu urban